Opera/teater i nye formater: Teaterkunstverkets liveness i HD-teknologiens tidsalder - Hov, Live (Peripeti, 2012)
The article deals with the relationship between actors/singers and spectators in mediatized versions of theatre and opera. A critical survey of these new genres constitutes the basis for a theoretical discussion about the liveness of theatrical experience, with references to texts by Auslander, Benjamin and Fischer-Lichte.